Mathematical Literacy Ability in Experiential Learning with Performance Assessment Based on Self-Efficacy (Universitas Negeri Semarang, 2021)
Mathematical literacy skills and self-efficacy are important for students to have in learning mathematics. To be able to help improve mathematical literacy and self-efficacy skills, a learning model is needed, namely experiential learning with performance assessment. This study aims to (1) analyze the quality of experiential learning models with performance assessment based on self-efficacy on mathematical literacy abilities, (2) describe students' mathematical literacy abilities on experiential learning with performance assessment based on self-efficacy. The method in this study is mixed methods with a concurrent embedded strategy, namely the qualitative method as the primary method. The population in this study were all students of class VII MTs N 2 Semarang by taking a sample of students VII-D as an experimental class and VII-E as a control class. Research data were analyzed by t test. The results showed that the average mathematics literacy ability of students in the experiential learning model learning class based on self-efficacy was more than the average mathematics literacy ability of students in the Discovery Learning class. Students who have low self-efficacy have not mastered the components of the mathematics literacy process to the maximum, students who have moderate self-efficacy are only able to master the ability to use mathematic tools and the other components of the mathematical literacy process are quite good. Students who have high self-efficacy are able to master the seven components of the process of mathematical literacy even though there are still two components whose completion is less than optimal.